Rapid implementation of a clinical decision-support workflow during the national blood culture bottle shortage - Saira Butt; Amy B. Kressel; Brian L. Haines; Katherine Merrill; Amber M. Ryan; Kenneth C. Gavina; Bree Weaver; Michael Kays; Molly Tieman; Margaret Muciarelli; Phillip Clapham (Infection Prevention in Practice)
Summary: Background: The United States Food and Drug Administration recently announced a national blood culture (BC) bottle shortage; the exact date of restoration is still being determined. Aim: Implement a workflow to mitigate the BC bottle shortage at our hospital. Methods: We created the following clinical decision support workflow in electronic medical record to help mitigate BC bottle use: (a) limit to two BC in 24 hours, (b) only repeat BC if 72 hours have passed from the prior sets, (c) do not repeat BC for coagulase-negative Staphylococcus bacteremia when considered a contaminant (i.e., no implanted vascular device), (d) do not repeat BC for Streptococcus bacteremia, (e) do not repeat cultures for Gram-negative rod bacteremia unless an unknown source, immunosuppression, or clinical worsening. Findings: Post implementation, our weekly average BC bottle use decreased to 29.5%. Conclusion: Within three weeks of the BC bottle shortage announcement, we successfully deployed evidence-based BC restrictions in the electronic medical record (EMR), reducing our BC orders by 29.5%. We encourage others to consider and potentially replicate our workflow to contribute to diagnostic stewardship.